THE VIEW OF THE FAMILIES ABOUT THE OLD AGE AND THE RELATIONSHIP WITH ELDERS (Fiep Bulletin - online, 2011)
This study aims to punctuate the look of the family on aging and elderly within the family. This is a descriptive of qualitative conducted with relatives of elderly residents of a nursing home resident and a lacking community in João Pessoa, Paraíba, Brazil that agreed to participate voluntarily in the research. The field research included the application of a questionnaire administered to 10 family members and systematic observation. It was observed that all family members understand aging as a mandatory stage of life. But family members who had their elderly institutionalized, believed that to become elderly would lose their autonomy and rights, therefore, kept the elderly far from their family environment, not bothering to leave him and abandon him in an institution . Now the family members of elderly resident, even in a precarious social context, prefer to live with them, whether they are healthy or not. The bonds of affection and solidarity are not affected by the context of poverty. They also report that the family environment is crucial for the elderly so that he can take the aging process less traumatic.
Keywords: Family; Elderly; Poverty